The mathematics of 3D buffering for simple geospatial primitives - Chen, Tet Khuan; Abdul Rahman, Alias (Faculty of Geoinformation Science and Engineering, 2003)
This paper describes an effort towards realizing 3D buffering operations for 3D GIS. The buffering is based on spatial data primitives of points, lines, and polygons. All the analytical solutions for the buffering is discussed in detail and form a major discussion of this paper. The mathematics, the geometry, and the algorithms involved will be presented. We have tested the approach by using photogrammetrically captured data sets and a commercial GIS package for visualization purpose. Finally, we present the outlook of the 3D analytical solutions for 3D GIS.